Using the theory of planned behavior to examine the environmental behavior of roadrunners in Taiwan - Chih-Jui Pai; Ben A. LePage; Eric Ng; Wei‑Ta Fang (Discover Sustainability)
Abstract Background Road running and similar community events boost local economies but also generate significant disposable waste, raising environmental concerns. According to the Theory of Planned Behavior, eco-friendly intentions are influenced by attitudes, subjective norms, and perceived behavioral control. This study explores these psychological factors among Taiwanese road runners, highlighting their ecological accountability and aiming to impact both theory and practice of environmental behavior towards societal sustainable development. Methods A total of 430 questionnaires were collected from people associated with a series of road-running events in Taiwan. Based on the Theory of Planned Behavior, the relationships between the key components such as attitude, subjective norms, perceived behavioral control, behavioral intention, and behavior were investigated. The survey questions were designed and adapted in accordance with the guidelines for Theory of Planned Behavior questionnaire construction proposed by Ajzen. Partial least squares—Structural Equation Modeling has been used in hundreds of studies across a wide range of disciplines and was used to explore these components and develop a pathway model. Results The results indicated that when females participate in road-running events, their perceived behavioral control, behavioral intention, and behavior regarding environmental protection are higher than those of the males that were sampled. Road-running participants who are aware of environmental road-running events exhibit better attitudes toward promoting environmental protection and more likely to be influenced by subjective norms. Older road-running event participants tend to outperform their younger counterparts in all the key components that were investigated in this study. Conclusions The findings supported the five hypotheses that were tested in this study. Moreover, when encouraging people to participate in road-running events, environmental intervention protection measures must be implemented to increase the public’s awareness and knowledge of environmental protection at these types of events.